William Shakespeare's The merchant of Venice El mercader de Venecia - Collins, Lynn, 1979-; Delhomme, Benoit; Fiennes, Joseph, 1970-; Irons, Jeremy, 1948-; Pacino, Al, 1940-; Pook, Jocelyn; Radford, Michael, 1946-; Robinson, Zuleikha, 1977-; Shakespeare, William, 1564-1616.; Columbia TriStar Home Entertainment (Firma); Sony Pictures Home Entertainment (Firma) (Culver City, Calif. : Columbia TriStar Home Entertainment : Distributed by Sony Pictures Home Entertainment, 2005)
En Venecia del siglo 16, un comerciante debe por defecto un gran préstamo de un abusador judío prestamista, para un amigo con ambiciones románticas, el vengativo amargamente acreedor exige un pago muy horrible.
DISPONIBLE
Originally released as a motion picture in 2004.
Special features: Audio commentary with director Michael Radford & actress Lynn Collins; making-of 'The merchant of Venice' featurette; weblink to the Teachers' Guide (a classroom guide); previews.
Director of photography, Benoit Delhomme ; editor, Lucia Zucchetti ; music, Jocelyn Pook ; costume designer, Sammy Sheldon ; production designer, Bruno Rubeo.
Al Pacino, Jeremy Irons, Joseph Fiennes, Lynn Collins, Zuleikha Robinson, Kris Marshall, Charlie Cox, Heather Goldenhersh, Mackenzie Crook, John Sessions, Gregor Fisher, Ron Cook, Allan Corduner, Anton Rodgers, David Harewood, Antonio Gil-Martinez.
MPAA rating: R; for some nudity.
Keywords: Shakespeare, William, -- 1564-1616.; Judíos -- Italia -- Teatro; Shylock (Personaje de ficción); Usura -- Teatro; Venecia (Italia) -- Teatro; Adaptation; Feature; Melodrama